2020
DOI: 10.36560/1312020978
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality of fig fruits using different edible coatings

Abstract: The Fig (Ficus carica L.) is a fruit produced worldwide for in in natura consumption and processing. The aim of this work was to evaluate the effect of edible coatings on the post-harvest qualities of fig fruit. The experiment was conducted at the Instituto Federal Goiano – Urutaí Campus, using figs from a orchard in the municipality of Silvania-GO. The fruits, after washing and sanitization, received edible coatings (polysaccharide, protein and lipid), constituting the treatments together with the control tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Contrary to the soluble solids content, the titratable acidity responded only to the storage period with a small increase from the beginning to the end of the 17-day storage period (Figure 3). Similarly, it was observed that figs' acidity did not change at all during the storage period (Pinto et al, 2020). However, this was not always observed in all fig cultivars, as may be seen in 'Bardakci' (Gözlekçi et al, 2008), 'Bursa Siyahi' (Ozkaya et al, 2014), 'Albacor' (Villalobos et al, 2018) and 'Qing Pi' (Song et al, 2020), the titratable acidity increased along the storage period, demonstrating that it might be a cultivar characteristic.…”
Section: Resultsmentioning
confidence: 77%
“…Contrary to the soluble solids content, the titratable acidity responded only to the storage period with a small increase from the beginning to the end of the 17-day storage period (Figure 3). Similarly, it was observed that figs' acidity did not change at all during the storage period (Pinto et al, 2020). However, this was not always observed in all fig cultivars, as may be seen in 'Bardakci' (Gözlekçi et al, 2008), 'Bursa Siyahi' (Ozkaya et al, 2014), 'Albacor' (Villalobos et al, 2018) and 'Qing Pi' (Song et al, 2020), the titratable acidity increased along the storage period, demonstrating that it might be a cultivar characteristic.…”
Section: Resultsmentioning
confidence: 77%